Chrysin Is Immunomodulatory and Anti-Inflammatory against Complete Freund's Adjuvant-Induced Arthritis in a Pre-Clinical Rodent Model - Muhammad Asif Faheem; Tasleem Akhtar; Nadia Naseem; Usman Aftab; Muhammad Shoaib Zafar; Safdar Hussain; Muhammad Shahzad; Glenda Carolyn Gobe (MDPI AG, 2023)
Chrysin (5,7-dihydroxyflavone) has many pharmacological properties including anti-inflammatory actions. The objective of this study was to evaluate the anti-arthritic activity of chrysin and to compare its effect with the non-steroidal anti-inflammatory agent, piroxicam, against complete Freund's adjuvant (CFA)-induced arthritis in a pre-clinical model in rats. Rheumatoid arthritis was induced by injecting CFA intra-dermally in the sub-plantar region of the left hind paw of rats. Chrysin (50 and 100 mg/kg) and piroxicam (10 mg/kg) were given to rats with established arthritis. The model of arthritis was characterized using an index of arthritis, with hematological, biological, molecular, and histopathological parameters. Treatment with chrysin significantly reduced the arthritis score, inflammatory cells, erythrocyte sedimentation rate, and rheumatoid factor. Chrysin also reduced the mRNA levels of tumor necrosis factor, nuclear factor kappa-B, and toll-like recepter-2 and increased anti-inflammatory cytokines interleukin-4 and -10, as well as the hemoglobin levels. Using histopathology and microscopy, chrysin reduced the severity of arthritis in joints, infiltration of inflammatory cells, subcutaneous inflammation, cartilage erosion, bone erosion, and pannus formation. Chrysin showed comparable effects to piroxicam, which is used for the treatment of rheumatoid arthritis. The results showed that chrysin possesses anti-inflammatory and immunomodulatory effects that make it a potential drug for the treatment of arthritis.